2018
DOI: 10.1002/btpr.2702
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of environmental impact of biologics manufacturing using process mass intensity analysis

Abstract: Process mass intensity (PMI) is a benchmarking metric to evaluate the efficiency of a manufacturing process, which is indicative of the environmental impact of the process. Although this metric is commonly applied for small molecule manufacturing processes, it is less commonly applied to biologics. In this study, an Excel based tool developed by the ACS GCI Pharmaceutical Roundtable was used to calculate PMI of different manufacturing processes for a monoclonal antibody (mAb). For the upstream process, three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…4(A)]. 4,5 Furthermore, AEX had the highest fraction of process‐related water consumption, whereas the contribution of all other unit operations to the PMI was due mainly to cleaning water. However, the more efficient AEX capture step in the extracellular process EX entailed the largest PMI savings compared to the intracellular process IN [Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4(A)]. 4,5 Furthermore, AEX had the highest fraction of process‐related water consumption, whereas the contribution of all other unit operations to the PMI was due mainly to cleaning water. However, the more efficient AEX capture step in the extracellular process EX entailed the largest PMI savings compared to the intracellular process IN [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the costs, the ecological footprint is an increasingly important factor in the evaluation of recombinant protein production processes. Recently, process mass intensity (PMI) was proposed as a metric to evaluate the resource efficiency of recombinant protein production 4,5 . The PMI relates the mass of consumed raw materials to the mass of produced protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the process mass intensity (PMI) is also calculated as an index of the overall process efficiency of the manufacturing process, specifically with respect to its environmental impact. This is given by the ratio between the total input mass to the process (buffers, raw material, and resin) (mass process ) and the mass of purified product (Cataldo et al, 2020; Madabhushi et al, 2018), as indicated in Equation (5): PMI (normalg/normalg)=mprocessmrecovered. $\mathrm{PMI}\unicode{x02007}({\rm{g}}/{\rm{g}})=\frac{{m}_{\mathrm{process}}}{{m}_{\mathrm{recovered}}}.$…”
Section: Methodsmentioning
confidence: 99%
“…The complexity of achieving carbon‐neutral bioprocessing has been highlighted by initial assessments (Budzinski et al, 2019 ; Pietrzykowski et al, 2013 ). For example, the first process mass intensity analysis showed bioprocesses to be heavily water intensive, where 90% of the mass was from water (Budzinski et al, 2019 ; Madabhushi et al, 2018 ) and 1 g of biological drug requires up to 65 L of water (Jungbauer & Walch, 2015 ). Lifecycle assessment (LCA) studies have demonstrated that single‐use (SU) technologies provide additional environmental impact advantages over the traditional stainless‐steel manufacturing, such as eliminating clean‐in‐place water usage, reducing HVAC energy usage through the use of closed systems and provide smaller footprint processing (Pietrzykowski et al, 2013 ).…”
Section: Sustainabilitymentioning
confidence: 99%